e-portfolios in the Cyprus Language Arts reformed curriculum: The teachers' perspective - Iolie Nicolaidou (My University, 2012)
The present study focuses on documenting the teachers’ perspective on the integration of paper-based and e-portfolios in the Language Arts primary school curriculum in Cyprus. This study is part of a larger research project which sought to explore how portfolio affordances (feedback, goal-setting, reflection and self-evaluation) related to students’ writing performance over time. The participants were three Language Arts teachers and 64 fourth grade students. One class (n1=20) created ePortfolios based on a repurposed Web2.0 tool (WordPress) and two classes (n2=23, n3=20) created paper-based portfolios. Students input their writing pieces in their portfolios throughout the academic year, shared their work to receive peer- and teacher-feedback and incorporated that feedback to revise their work. Students then engaged in self-evaluation, self-reflection, and goal-setting. The present study’s aim was the documentation of the teachers’ perspective on portfolio integration in the Language Arts primary school curriculum in Cyprus. Data sources included two videotaped teachers’ interviews and the researcher’s field notes. Teachers were asked to reflect on their teaching practices and identify benefits and obstacles of portfolio implementation. Additional sources of data, used for triangulation purposes, included the portfolio artifacts: 514 student-essays, 2822 instances of peer feedback, 3346 instances of teacher feedback, 477 goals, 308 self-evaluations and 162 reflections. Teacher interviews were transcribed in English using a qualitative research analysis tool (Transana 2.22). The qualitative analysis followed an inductive grounded theory approach to build an understanding of benefits and obstacles of portfolio implementation as perceived by teachers. A systematic methodology of open, axial, and selective coding was followed that resulted in the generation of a discursive set of propositions describing the interrelationships illustrated in the coding paradigm. The study showed that as portfolio pedagogy was an innovation in the Greek-Cypriot context, teachers had some uncertainty about the process and concerns about the high time demands of portfolios. Students’ difficulties to engage in portfolio pedagogy, the lack of adequate computer equipment, students’ low level of typing skills, and peer feedback competitiveness were factors that influenced the teachers’ decision not to consider e-portfolios as an option. Teachers encouraged goal setting and self-evaluation to a great extent, provided students with opportunities for peer feedback and second drafts of their work but did not promote students’ reflection. Teachers reported an improvement in students’ writing performance and skills in goal setting, self-evaluation and accepting and providing peer feedback, all of which were evident in students’ paper-based portfolios. Despite initial hesitation, both teachers would consider using Web2.0 e-portfolios to facilitate students’ working on multiple drafts, increase parental involvement, encourage peer feedback and take advantage of the motivational role that computers have for students of this age-group. Based on teachers’ perceptions, suggestions on improving the pedagogy behind the use of portfolios are suggested to overcome identified limitations. Implications for practice and guidelines based on a bottom-up approach that could facilitate a large-scale implementation of paper-based and e-portfolios in Cyprus in the future are offered.
Keywords: Student-Portfolios; Teachers’ Perspective; Process Portfolio Pedagogy; E-Portfolios; Primary Education